Improved quantitative detection of biotin‐labeled red blood cells by flow cytometry. Issue 8 (6th June 2019) - Donnenberg, Albert D.; Kanias, Tamir; Triulzi, Darrell J.; Dennis, Catherine J.; Meyer, E. Michael; Gladwin, Mark
Abstract : BACKGROUND: Biotin‐labeled red blood cells (BioRBC) can be tracked after transfusion, providing a convenient and safe way to measure RBC survival in vivo. RBC survival is of interest for determining optimal blood storage conditions and for assessing the impact of genetic and biologic variants in blood donors on the survival of transfused RBCs. Here we present an improved, platform‐independent assay for quantifying biotin on BioRBC. This approach is also useful for detecting BioRBC in peripheral blood samples as rare events. STUDY DESIGN AND METHODS: We optimized the signal‐to‐noise ratio of the detecting reagent (phycoerythrin‐conjugated streptavidin [SA‐PE]) by determining the SA‐PE concentration yielding the greatest separation index between BioRBC and unlabeled RBCs. We calibrated the fluorescence intensity measurements to molecules of equivalent soluble fluorochrome (MESF), a quantitative metric of fluorochrome binding and therefore of biotin bound per RBC. We then characterized the limit of blank and limit of quantification (LoQ) for BioRBC labeled at different densities. RESULTS: Biotin‐labeled RBCs at sulfo‐NHS‐biotin concentrations of 3 to 30 μg/mL (27‐271 nmol/mL RBCs) ranged from approximately 32, 000 to 200, 000 MESF/RBC. The LoQ ranged from one in 274, 000 to one in 649, 000, depending on biotin‐labeling density. CONCLUSION: Increased sensitivity to detect BioRBC may facilitate tracking over longer periods and/or reduction of the BioRBC dose. Total RBC‐bound biotin dose has been shown to correlate with the likelihood of developing antibodies to BioRBC. Lowering the dose of labeled cells may help avoid this eventuality.